Avaliação da calibração em LA-ICP-MS usando papel filtro para análise de plantas - Nunes, Matheus Augusto Gonçalves (2015)
In this work, a new calibration strategy was investigated for the determination of As, Ba, Cd, Ce, Co, Cr, Cu, La, Mn, Ni, Pb, Se, Sr, Tl, V and Zn in medicinal plants by laser ablation and inductively coupled plasma mass spectrometry (LA-ICP-MS). The main innovation of this work was the use of filter paper for calibration, due to its similarities with botanical samples regarding to carbon concentration and distribution through both materials. These conditions allowed the use of 13C as a reference element during the analysis by LA-ICP-MS. An advantage of the proposed procedure is the possibility of using aqueous standard solutions to perform the calibration, which were placed on the filter paper and dried before ablation, avoiding the time-consuming procedures of standard preparation for LA-ICP-MS analysis. In this way, parameters as analyte signal normalization with 13C, use of dry or wet aerosol during the ablation, carrier gas flow rate, laser energy, spot size, pressure applied for pellet preparation and calibration range were investigated. Accuracy of LA-ICP-MS determinations were evaluated by analysis of certified reference materials of vegetal composition, as well as by comparison with results obtained by ICP-MS and inductively coupled plasma optical emission spectrometry (ICP OES) after microwave assisted sample digestion. Limits of detection obtained by LA-ICP-MS were 1 to 2 orders higher than those obtained by ICP-MS with pneumatic nebulization. Besides the application of LA-ICP-MS for multielement analysis of plant samples, the method was successfully applied for imaging of elemental distribution in a leaf of medicinal plant.